Effect of ultrasound and microwave assisted vacuum frying on mushroom (Agaricus bisporus) chips quality. (October 2018) - Devi, Shoma; Zhang, Min; Law, Chung Lim
Abstract: The effect of ultrasound on frying rate and product quality of fried mushroom chips (FMC) was investigated using microwave assisted vacuum frying (MVF). To determine the effectiveness of ultrasound during frying at different microwave power levels (800, 900 and 1000 W) and different frying temperature (80, 85 and 90 ℃), quality parameters (moisture loss rate, oil uptake rate, texture, color and microstructure) of the FMC obtained from vacuum frying (VF), MVF and ultrasound assisted microwave vacuum frying (UMVF) were analyzed and compared. It was found that UMVF accounts for the highest moisture loss rate with the increase of microwave power and frying temperature. Considering the oil uptake rate, UMVF could reduce oil content by 16–20% compared to VF and MVF. UMVF chips also had better texture and the most acceptable color characteristics among the frying techniques studied. The optimum condition of 1000 W and 90 ℃ achieved a higher moisture evaporation rate and lower oil content. Microstructure observations showed that the surface structures of UMVF fried samples were the smoothest and also showed less distorted cells. Based on the parameters evaluated, UMVF mushroom chips had the best-fried matrices as well as accelerated frying rate, lower oil uptake, improved texture and color. Highlights: Application of ultrasound during microwave vacuum frying (MVF) significantly increased moisture loss rate during frying. Ultrasound assisted microwave vacuum frying (UMVF) had better color and higher crispness. Oil uptake was lower for MVF and UMVF than traditional vacuum frying (VF). The cellular structure and integrity of cell walls in chips was better preserved using UMVF.